Enhancing Descriptive Writing Skills of EFL Junior High School Students through Clustering Technique - I Gde Putu Agus Pramerta; Thara Arnetta; Dewa Ayu Ari Wiryadi Joni (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2026)
This study aimed to improve the descriptive writing skills of seventh-grade students at SMPN 2 Kuta Utara in the 2025/2026 academic year through the implementation of the clustering technique. The study employed a Classroom Action Research (CAR) design consisting of two cycles and involved 38 students as the research participants. Data were collected through writing tests (pre-test, post-test 1, and post-test 2) and a questionnaire to examine students’ perceptions of the technique. The data were analyzed using descriptive quantitative analysis by calculating mean scores and percentages, supported by classroom observations. The findings revealed a gradual improvement in students’ writing performance across the research cycles. The mean score of the pre-test in the pre-cycle was 57.36, indicating that students’ initial writing ability was relatively low. After the implementation of the clustering technique in Cycle I, the mean score increased to 63.89. A more significant improvement was observed in Cycle II, where the mean score reached 75.08, and 31 out of 38 students successfully achieved the minimum passing grade. Furthermore, the questionnaire results showed that the majority of students expressed positive perceptions toward the use of the clustering technique and reported increased motivation in writing descriptive paragraphs. These findings indicate that the clustering technique effectively supports students in generating ideas, organizing their thoughts, and developing descriptive texts. Therefore, it can be concluded that the clustering technique is an effective strategy for improving students’ descriptive writing skills and increasing their engagement in the writing learning process.